Historical building acoustical retrofit: An experimental examination of traditional wooden floors. Issue 3 (September 2016) - Queirós, Dóris; Calejo Rodrigues, Rui; Pereira, Nelson
Historic buildings that regularly characterize the centre of our cities present us the challenge of being updated without losing their uniqueness. Acousticians frequently find themselves at the centre of this challenge, facing traditional solutions that must fulfil contemporary acoustical requirements. In order to apply technical improvements to enhance the performance of traditional solutions, the first step is to understand how these solutions work and perform in real-life conditions. Traditional solutions were conveniently tested by site measurements for validation. Airborne sound insulation (DnT, w ) and impact sound insulation (L nT, w ′ ) tests were performed on 13 similar wooden floors. The same wooden floor was constructed at the Faculty of Engineering in University of Porto's acoustic chamber in order to study its acoustical behaviour without the influence of flanking transmissions. Wooden floor improvement solutions were tested through the addition of airborne and impact sound insulation favouring materials. Airborne sound insulation (Rw ) and impact sound insulation (Lnw ) tests were performed on six solutions for the improvement of the traditional wooden floors. Traditionally, in Portuguese historical buildings, the lack of knowledge of the traditional solutions' technical characteristics is sometimes the reason for demolishing these solutions. Adapting traditional solutions to current standards of comfort can become arduous since the information on the performance of these solutions is unknown. The potential demonstrated by these enhanced traditional solutions predicted a shift in current paradigms and will allow acousticians to support the challenge of historic building retrofit.